Photoprotective effect and acute oral systemic toxicity evaluation of the novel heterocyclic compound LQFM048 - Vinhal, Daniela C.; Avila, Renato Ivan de; Vieira, Marcelo S.; Luzin, Rangel M.; Quintino, Michelle P.; Nunes, Liliane M.; Chaves Ribeiro, Antonio Carlos; Camargo, Henrique Santiago de; Pinto, Angelo C.; Santos Junior, Helvecio M. dos; Chiari, Bruna G. [UNESP]; Isaac, Vera [UNESP]; et al. (Elsevier B.V., 2016)
The new heterocyclic derivative LQFM048 (3) (2,4,6-tris ((E)-ethyl 2-cyano-3-(4-hydroxy-3-methoxyphenyl)acrylate)-1,3,5-triazine) was originally designed through the molecular hybridization strategy from Uvinul (R) T 150 (1) and (E)-ethyl 2-cyano-3-(4hydroxy-3-methoxyphenyl)acrylate (2) sunscreens, using green chemistry approach. This compound was obtained in global yields (80%) and showed an interesting redox potential. In addition, it is thermally stable up to temperatures around 250 degrees C. It was observed that LQFM048 (3) showed a low degradation after 150 min of sunlight exposure at 39 degrees C, whereas the extreme radiation conditions induced a considerable photodegradation of the LQFM048 (3), especially when irradiated by VIS and VIS + UVA. During the determination of sun protection factor, LQFM048 (3) showed interesting results, specially as in association with other photoprotective compounds and commercial sunscreen. Additionally, the compound (3) did not promote cytotoxicity for 3T3 fibroblasts. Moreover, it was not able to trigger acute oral systemic toxicity in mice, being classified as a compound with low acute toxicity hazard (2.000 mg/kg > LD50 < 5.000 mg/kg). Therefore, this compound synthesized using green chemistry approach is promising showing potential to development of a new sunscreen product with advantage of presenting redox potential, indicating antioxidant properties. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Heterocyclic derivative; Molecular hybridization; Photoprotection; Sunscreen; Green chemistry